2022
DOI: 10.1155/2022/1898844
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Ameliorates Reactive Oxygen Species-Induced Platelet Storage Lesions

Abstract: Platelet transfusion is a life-saving therapy to prevent bleeding; however, the availability of platelets for transfusion is limited by the markedly short shelf life owing to the development of platelet storage lesions (PSLs). The mechanism of PSLs remains obscure. Dissection of the intracellular biological changes in stored platelets may help to reduce PSLs and improve platelet transfusion efficiency. In the present study, we explore the changes of stored platelets at room temperature under constant agitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This probably indicates that the cell death process begins in the parasite. Previous studies have shown that oxidative stress also leads to the generation of autophagic responses [49][50][51]. Therefore, we speculate that toltrazuril may lead to parasite autophagy by enhancing oxidative stress.…”
Section: Discussionmentioning
confidence: 65%
“…This probably indicates that the cell death process begins in the parasite. Previous studies have shown that oxidative stress also leads to the generation of autophagic responses [49][50][51]. Therefore, we speculate that toltrazuril may lead to parasite autophagy by enhancing oxidative stress.…”
Section: Discussionmentioning
confidence: 65%
“…There are some well-defined platelet regulatory factors, for example, NO, prostacyclin (PGI2), adenosine, and ROS, that play roles in platelet activation. For instance, excess ROS generation and oxidative stress during platelet storage are closely related to PSL . ROS can cause activation of the stored platelets through multiple pathways: (1) intraplatelet ROS trigger the activation of αIIbβ3, which causes platelet aggregation upon activation; (2) ROS scavenge NO in platelets, resulting in platelet activation; (3) ROS damage the mitochondrial membrane integrity and compromise the functions of nucleic acids, lipids, and proteins in the platelets, resulting in platelet apoptosis. , Mitochondrial dysfunction affects the normal synthesis of ATP and the bioenergetic state of platelets .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 ROS are generated by NADPH oxidase, p66Shc oxidase, COX oxidase, and the mitochondrial respiratory chain. 11 Increased ROS levels can lead to platelet apoptosis, 12 activation, 13 loss of platelet adhesiveness and aggregation to reactive matrixes, 14 and a decline in platelet quality. 15 Notably, the concentrated platelets stored in an incubator and agitator undergo deleterious changes due to the physical interaction among the platelets and between them with the environment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation